Characteristic Of Tweek Atmospherics Observed in Mid-latitude Using AWESOME VLF Receiver - Yusop, Norbayah; Mohd Aris, Nor Azlan; Mohd Chachuli, Siti Amaniah; Meor Said, Maizatul Alice (Maxwell Scientific Publications, 2014)
This study presents the analysis of tweek atmospherics received by AWESOME VLF receiver at station of Gakona (62.71°N, 143.99°W) during four months observation from January to April 2011. Tweek which originates from lightning discharge are used to monitor the nighttime D-region ionosphere using the fundamental cut-off frequency to measure the variations of the lower ionosphere’s reflection height, the equivalent electron density at the reflection height and the propagation distance travel by tweeks. In this study, a total of 1316 tweeks are analyzed and from the analysis, it shows that equinox’s season has the highest tweek occurrence compared to winter season in March and April. The maximum harmonic (m) of t weeks is found to be up to fourth (m = 4) and tweeks with mode number one (m = 1) are more dominantly occurred. Our observations indicate that the equivalent electron densities for tweeks varies from 22-27 eL/cm3 in the altitude ranged of 75 to 91 km and demonstrate that these ELF/VLF signals travel considerable distances up to 6700 km from the causative lightning discharges. The ionospheric parameters for three locations (high, middle and low latitude respectively) were compared and the results show that they are almost consistent for all the locations.